2020
DOI: 10.1039/c9ta09307a
|View full text |Cite
|
Sign up to set email alerts
|

Temperature tunability in Sr1−xCaxFeO3−δ for reversible oxygen storage: a computational and experimental study

Abstract: Sr1−xCaxFeO3−δ oxygen carriers can be designed for specific reaction conditions through selective Ca2+ inclusion at the A-site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 48 publications
5
29
0
Order By: Relevance
“…Similar results have been demonstrated for the addition of cobalt as well [5,19] . However, both substitutions sacrifice the overall amount of oxygen that can be held by the SrFeO 3 lattice to yield these thermodynamic gains, [1,2,4,16–20] but we recognize the important effects that both calcium and cobalt doping can have on SrFeO 3 performance.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…Similar results have been demonstrated for the addition of cobalt as well [5,19] . However, both substitutions sacrifice the overall amount of oxygen that can be held by the SrFeO 3 lattice to yield these thermodynamic gains, [1,2,4,16–20] but we recognize the important effects that both calcium and cobalt doping can have on SrFeO 3 performance.…”
Section: Introductionsupporting
confidence: 80%
“…We, among others, have detailed the effects of both Ca‐doping and dual‐doping individually in the SrFeO 3 ‐based system [1,2,4,5,16–20] . It has been observed that the addition of Ca can greatly decrease operating temperature by lowering the enthalpy of oxidation [1,20] . Similar results have been demonstrated for the addition of cobalt as well [5,19] .…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations